1995
DOI: 10.1182/blood.v85.9.2619.bloodjournal8592619
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood progenitor cell (PBPC) counts during steady-state hematopoiesis allow to estimate the yield of mobilized PBPC after filgrastim (R-metHuG-CSF)-supported cytotoxic chemotherapy [see comments]

Abstract: Peripheral blood progenitor cells (PBPC) can be mobilized using cytotoxic chemotherapy and cytokines. There is a substantial variability in the yield of hematopoietic progenitor cells between patients. We were looking for predictive parameters indicating a patient's response to a given mobilization regimen. Multiparameter flow-cytometry analysis and clonogenic assays were used to examine the hematopoietic progenitor cells in bone marrow (BM) and peripheral blood (PB) before filgrastim (R-metHuG-CSF; Amgen, Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…After immunomagnetic CD34 + cell selection, the percentage of CD34 + cells in BM was 89.18% ± 3.17% and 91.05% ± 2.26% in LP samples. When we analyzed the coexpression on CD34 + cells of the lineage-associated and maturation-associated antigens CD7, CD19, CD33, CD38, CD45RA, CDw90, CD117, and HLA-DR as well as the activation molecule CD71, we found that greater than 95% of hematopoietic cells in both compartments coexpressed the HLA-DR and CD38 antigens, whereas in LP compared to BM, the proportion of phenotypically primitive CD34 + /CDw90 + cells and of myeloid precursors (i.e., CD34 + /CD33 + ) was significantly greater at the expense of B-lymphocyte precursors (CD34 + /CD19 + ), as already reported [28,29] (data not shown).…”
Section: Progenitor Cell Characteristics In Steady-state Bm and Mobilsupporting
confidence: 89%
“…After immunomagnetic CD34 + cell selection, the percentage of CD34 + cells in BM was 89.18% ± 3.17% and 91.05% ± 2.26% in LP samples. When we analyzed the coexpression on CD34 + cells of the lineage-associated and maturation-associated antigens CD7, CD19, CD33, CD38, CD45RA, CDw90, CD117, and HLA-DR as well as the activation molecule CD71, we found that greater than 95% of hematopoietic cells in both compartments coexpressed the HLA-DR and CD38 antigens, whereas in LP compared to BM, the proportion of phenotypically primitive CD34 + /CDw90 + cells and of myeloid precursors (i.e., CD34 + /CD33 + ) was significantly greater at the expense of B-lymphocyte precursors (CD34 + /CD19 + ), as already reported [28,29] (data not shown).…”
Section: Progenitor Cell Characteristics In Steady-state Bm and Mobilsupporting
confidence: 89%
“…Our initial report on the predictive value of steady-state PB CD34 þ cell counts for the PBPC yield after mobilization with chemotherapy and G-CSF or G-CSF alone has been confirmed by other groups (Fruehauf et al, 1995;Brown et al, 1996;Husson et al, 1996;Haug et al, 1997). The present study on a large number of patients allowed an assessment of the determinants of premobilization progenitor cell levels and PBPC mobilization in different disease entities.…”
Section: Discussionsupporting
confidence: 56%
“…᭧ 1999 Blackwell Science Ltd, British Journal of Haematology 105: [786][787][788][789][790][791][792][793][794] G-CSF-supported chemotherapy (Fruehauf et al, 1995;Haug et al, 1997) or G-CSF mobilization alone (Husson et al, 1996;Brown et al, 1996). In this trial we have studied the possible determinants, such as previous therapy, on the steady-state CD34 þ cell levels.…”
Section: Steady-state Pbpc For Estimation Of the Mobilization Yieldmentioning
confidence: 99%
“…The efficacy of different mobilization strategies and the quality of the mobilized products are now subjects under intensive study. The dose of myelosuppressive chemotherapy (Kotasek et al, 1992;Rowlings et al, 1992), the addition of haemopoietic growth factors (Siena et al, 1989), bone marrow involvement by underlying disease (Shepherd et al, 1991), prior chemotherapy (To et al, 1990;Haas et al, 1994) and pre-mobilization peripheral blood progenitor level (Fruehauf et al, 1995) are factors which have been proposed as important determinants on the harvest's yield. However, data from randomized prospective studies comparing the efficacy of different mobilization regimens are still lacking.…”
Section: Discussionmentioning
confidence: 99%